Rescue of autoimmune hepatitis by soluble MHC class II molecules in an altered concanavalin A‐induced experimental model - Bakela, Katerina (Animal Model Exp Med, 2020)
BACKGROUND: Soluble major histocompatibility complex class II (sMHCII) molecules have been described to maintain tolerance through the suppression of autoreactive T lymphocytes. In order to evaluate their ability to rescue autoimmune hepatitis (AIH) symptoms, the present work attempted to administer sMHCII molecules to an in vitro as well as in vivo concanavalin A (ConA)‐induced AIH model. METHODS: The in vitro AIH model consisted of splenocyte stimulation with ConA in the presence or absence of serum‐isolated sMHCII molecules. An in vivo ConA‐modified model with or without sMHCII treatment was developed. The cytokine profile in culture supernatants and serum was tested by ELISA. Cell markers were evaluated by immunofluorescence, while cell proliferation by tritiated thymidine uptake. AIH symptoms were assessed by daily observations for the establishment of a disease severity scoring system and liver histology was evaluated using a biomolecular imager. RESULTS: The presence of sMHCII molecules in the ConA‐stimulated cell cultures leads to a significant reduction of cell proliferation. The administration of sMHCII molecules to the ConA‐treated animals showed a significant reduction in the levels of IL‐2, IL‐4, and IL‐10, as well as a decrease in the number of spleen CD4(+) and CD8(+) cells. Upon development of a scoring system, it was shown that the sMHCII treatment was accompanied by a slower progression of the disease, while rescuing fibrotic liver morphology. CONCLUSION: The results presented in this study confirm the ability of sMHCII proteins to alleviate autoimmune hepatitis, possibly highlighting new therapeutic approaches for autoimmune diseases.